Systems thinking in online travel agency of supplier relationship management - Ariya P. (2017)
Copyright © 2016 Inderscience Enterprises Ltd. Tourism industry nowadays has involved information technology as a useful part in trading. Many tourism services have developed a new kind of business called 'online travel agencies (OTAs)'. This kind of business greatly affects tourism industry and has become a mediator between customers and tourism suppliers. One of the essential knowledge in preceding the businesses of OTAs is supplier relationship management (SRM) method. The said knowledge is dynamical and is changing over time because tourism industry has many complicated relationships. Therefore, knowledge management of SRM process needs systems thinking: a learning organisation implementation tool for creating innovation, to explain relations between factors in two major system archetypes in the process which are: 1) systematised selection, which is a supplier selection process; 2) supplier relationship management, which is a knowledge sharing process. Both archetypes were used to create strategy plans to manage business relations between OTAs and suppliers in Chiang Mai.